Question
upstudy study bank question image url

For the given functions, find \( (f \circ g)(x) \) and \( (g \circ f)(x) \) and the domain of each. \( f(x)=x^{3}-8 x^{2}+2 x+7, g(x)=x+1 \) \( (f \circ g)(x)=\square \)

Ask by Chadwick Nguyen. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( (f \circ g)(x) = x^{3} - 5x^{2} - 11x + 2 \) with domain all real numbers. \( (g \circ f)(x) = x^{3} - 8x^{2} + 2x + 8 \) with domain all real numbers.

Solution

We are given the functions   f(x) = x³ – 8x² + 2x + 7   g(x) = x + 1 Step 1. Find (f ∘ g)(x): By definition, (f ∘ g)(x) = f(g(x)). Since g(x) = x + 1, we have:   f(g(x)) = f(x + 1) = (x + 1)³ – 8(x + 1)² + 2(x + 1) + 7 Now, expand each term: • (x + 1)³ = x³ + 3x² + 3x + 1 • (x + 1)² = x² + 2x + 1 Substitute these into f(x + 1):   f(x + 1) = (x³ + 3x² + 3x + 1) – 8(x² + 2x + 1) + 2x + 2 + 7 Distribute –8:   = x³ + 3x² + 3x + 1 – 8x² – 16x – 8 + 2x + 2 + 7 Now combine like terms: • x³ term:   x³ • x² terms:   3x² – 8x² = –5x² • x terms:   3x – 16x + 2x = –11x • Constants:  1 – 8 + 2 + 7 = 2 Thus, we obtain:   (f ∘ g)(x) = x³ – 5x² – 11x + 2 Since both f and g are polynomials, their domains are all real numbers. Therefore, the domain of (f ∘ g)(x) is all real numbers, ℝ. Step 2. Find (g ∘ f)(x): By definition, (g ∘ f)(x) = g(f(x)). Since g(x) = x + 1, we find:   g(f(x)) = f(x) + 1 Substitute f(x):   = (x³ – 8x² + 2x + 7) + 1   = x³ – 8x² + 2x + 8 Again, the domain of (g ∘ f)(x) is ℝ since f and g are both polynomials. Final Answer:   (f ∘ g)(x) = x³ – 5x² – 11x + 2, with domain ℝ.   (g ∘ f)(x) = x³ – 8x² + 2x + 8, with domain ℝ.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find \( (f \circ g)(x) \), you substitute \( g(x) \) into \( f(x) \). So, \[ (f \circ g)(x) = f(g(x)) = f(x+1) \] Calculating this: \[ f(x+1) = (x+1)^3 - 8(x+1)^2 + 2(x+1) + 7 \] Expanding \( (x+1)^3 = x^3 + 3x^2 + 3x + 1 \) and \( (x+1)^2 = x^2 + 2x + 1 \): \[ -8(x+1)^2 = -8(x^2 + 2x + 1) = -8x^2 - 16x - 8 \] Combining all the parts: \[ f(x+1) = (x^3 + 3x^2 + 3x + 1) - (8x^2 + 16x + 8) + (2x + 2) + 7 \] \[ = x^3 + 3x^2 - 8x^2 + 3x - 16x + 2x + 1 - 8 + 2 + 7 \] \[ = x^3 - 5x^2 - 11x + 2 \] So, \[ (f \circ g)(x) = x^3 - 5x^2 - 11x + 2 \] The domain of \( (f \circ g)(x) \) is all real numbers, \( \mathbb{R} \), since both \( f(x) \) and \( g(x) \) are polynomials. Now for \( (g \circ f)(x) \): \[ (g \circ f)(x) = g(f(x)) = g(x^3 - 8x^2 + 2x + 7) \] Calculating this: \[ g(f(x)) = (x^3 - 8x^2 + 2x + 7) + 1 = x^3 - 8x^2 + 2x + 8 \] So, \[ (g \circ f)(x) = x^3 - 8x^2 + 2x + 8 \] The domain of \( (g \circ f)(x) \) is also all real numbers, \( \mathbb{R} \), since both functions are polynomials as well. In summary: \[ (f \circ g)(x) = x^3 - 5x^2 - 11x + 2 \] \[ (g \circ f)(x) = x^3 - 8x^2 + 2x + 8 \] Domains: \( \mathbb{R} \) for both.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy